Overlooked Source of Shoulder Pain: Pectoralis Minor Myofascial Trigger Points and Dry Needling Efficacy - Akkuş, İlknur (The European Research Journal, 2026)
Dear Editor, Shoulder pain is one of the most common causes of musculoskeletal pain. It is most often associated with rotator cuff tendinopathy, subacromial impingement syndrome, or cervical radiculopathy [1]. In some patients, despite persistent shoulder pain, imaging studies revealed no significant pathology. Furthermore, the response to standard treatments (such as analgesic medication and physical therapy) was low. In such cases, the often overlooked clinical presentation of myofascial pain syndrome originating from the Pectoralis Minor (PM) muscle should be considered. The pectoralis minor muscle is located in proximity to the brachial plexus nerves and the axillary artery and vein; therefore, it is commonly associated with thoracic outlet syndrome and neurovascular compression in the literature. Consequently, related conditions are often described using the term “pectoralis minor syndrome”.